The effect of CRD method and auxiliary construction on surface settlement in shallow-buried tunnels - Zhang, Lin; Pan, Yuangui; Chen, Kezhu; Zheng, Guoqiang; Gao, Yang; Chen, Peng; Zhong, Guoxiang; Chen, Panfeng; Xu, Fengshou; Zhang, Yong; Nan, Guangyu; Xue, Haobo; et al. (Frontiers in Earth Science, 2023)
Several engineering practices have shown that the excavation of shallow-buried tunnels beneath major roads, as well as the selection of appropriate engineering measures and construction methods, has a significant impact on road surface settlement. Therefore, field monitoring and numerical simulation are adopted in this study to analyze the effect of the cross diaphragm (CRD) excavation method on surface settlement for the under-construction Yüan 1 railroad tunnel. The findings show that during the excavation of the four divisions of the CRD excavation method for shallow-buried tunnels, the amount of surface settlement caused by the excavation of part 1 accounts for 40% of the total surface settlement, followed by the excavation of part 3, accounting for 30% of the total surface settlement, and the difference between the excavation of parts 2 and 4 is insignificant, with part 2 slightly larger than part 4. The main influence of the CRD method on surface settlement for shallow-buried tunnels is 0.64–0.86 times the cavity diameter from the tunnel median, within which the final surface settlement caused by excavation is within the same horizontal range, and beyond which the surface settlement is prone to dramatically decline. By applying advanced grouting and adjusting the construction method of CRD based on the monitoring data, the effect of the CRD excavation method on surface settlement can be controlled.